Entrepreneurial Opportunity Recognition: a cause and outcome exploration of the influence of profit motives on entrepreneurial activities in France. - Dantec, Alexandre Ronan (2008)
In addition to enrich the individuals undertaking business ventures, entrepreneurial activities have been reckoned as benefiting the whole economic development (Gibb, 1996) through creative destruction (Schumpeter, 1950) and job creation (Burns, 2008).